Evidence for Cognitive Decline in Chronic Pain: A Systematic Review and Meta-Analysis - Zhang, Xueying; Gao, Rui; Zhang, Changteng; Chen, Hai; Wang, Ruiqun; Zhao, Qi; Zhu, Tao; Chen, Chan (Frontiers in Neuroscience, 2021)
Background: People with chronic pain sometimes report impaired cognitive function, including a deficit of attention, memory, executive planning, and information processing. However, the association between chronic pain and cognitive decline was still not clear. Our study aimed to assess the association of chronic pain as a risk factor with cognitive decline among adults. Methods: We included data from clinical studies. Publications were identified using a systematic search strategy from PubMed, EMBASE, and Cochrane Library databases from inception to October 10, 2020. We used the mean cognitive outcome data and the standard deviations (SD) from each group. The standardized mean difference (SMD) or odds ratio (OR) and 95% confidence intervals (CI) were performed for each cognitive decline outcome. I2 values were assessed to quantify the heterogeneities. Results: We included 37 studies with a total of 52373 patients with chronic pain and 80434 healthy control participants. Because these studies used different evaluative methods, we analyzed these studies respectively. The results showed chronic pain was associated with cognitive decline when the short form 36 health survey questionnaire (SF-36) mental component summary (SMD=-1.50, 95% CI=-2.19 to -0.81), the Montreal cognitive assessment (MOCA) (SMD=-1.11, 95% CI=-1.60 to -0.61), performance validity testing (PVT) (SMD=3.05, 95% CI=1.74 to 4.37) or operation span (OSPAN) (SMD=-1.83, 95% CI=-2.98 to -0.68) were used. However, we got opposite results when the studies using International Classification of Diseases and Related Health Problems (ICD) classification (OR=1.58, 95% CI=0.97 to 2.56), the Mini-Mental State Examination (MMSE) (SMD=-0.42, 95% CI=-0.94 to 0.10; OR=1.14, 95%CI=0.91 to 1.42) and Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) memory component (SMD=-0.06, 95%CI=-0.37 to 0.25). Conclusion: There may be an association between chronic pain and the incidence of cognitive decline when some cognitive evaluative methods were used such as SF-36, MOCA, PVT, and OSPAN.